Corporate governance and business performance: Evidence for the Romanian economy - Achim, Monica-Violeta; Borlea, Sorin-Nicolae; Mare, Codruţa (Journal of Business Economics and Management, 2016)
Our finding contributes towards the understanding of movements regarding the adoption of corporate governance practice in emerging countries such as Romania and its impact on business performances of a company. We have developed two econometric models to assess the business performances of the companies listed on Bucharest Stock Exchange, in order to point out the impact of corporate governance on business performances. Our results are inconsistent for the period 2001–2011, but if we consider only 2011, the results document a positive correlation between corporate governance quality and market value of companies, such it is reflected by Tobin’s Q. Therefore, our results contribute to the studies relating corporate governance and business performances, as it confirms a positive relationship between the two variables which appears once the Romanian emerging economy has began to adopt the best corporate governance practices. Firstly, our research has important implications for managers in order to know that the adoption of the best corporate governance practices could contribute to the financial success of the firm. Secondly, the results are useful for any investor who needs to consider the quality of corporate governance as a good predictor for the best rate of return of theirs investments. Moreover, our findings have also implications on policy-makers and regulatory authorities in European developing countries and offer them a barometer of adopting the best corporate governance practices in European space. First published online: 17 Mar 2015